2005
DOI: 10.1002/bip.20274
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular order following binding of the dichroic birefringent sulfonic dye Ponceau SS to collagen fibers

Abstract: The optical anisotropies (linear dichroism or LD and birefringence) of crystalline aggregates of the sulfonic azo-dye Ponceau SS and of dye complexed with chicken tendon collagen fibers were investigated in order to assess their polarizing properties and similarity to liquid crystals. In some experiments, the staining was preceded by treatment with picric acid. Crystalline fibrous aggregates of the dye had a negative LD, and their electronic transitions were oriented perpendicular to the filamentary structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 12 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…Although previous studies have demonstrated that the macromolecular reorganization of the collagen fibers in the muscle, tendon, bone, and cartilage can be evaluated by measuring birefringence using polarized light microscopy [15][16][17][18][19][20], few studies have investigated the macromolecular organization of the ICT after periods of immobilization by analyzing birefringence [20,21], which is considered to be an accurate morphological evaluation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated that the macromolecular reorganization of the collagen fibers in the muscle, tendon, bone, and cartilage can be evaluated by measuring birefringence using polarized light microscopy [15][16][17][18][19][20], few studies have investigated the macromolecular organization of the ICT after periods of immobilization by analyzing birefringence [20,21], which is considered to be an accurate morphological evaluation technique.…”
Section: Introductionmentioning
confidence: 99%
“…The filaments at the innermost region of the inner layer of the cocoon wall treated with the Ponceau SS solution stained light pink ( Fig. 2A-C), demonstrating presence of protein electropositive radicals (Vidal and Mello, 2005). This response also occurred in the laminar structure and encasing bubble elements of the foamy structures in the intermediate layer ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Total protein electropositive radicals were investigated in sections stained with a 0.025% Ponceau SS (Sigma, St. Louis, MO, USA) solution in 3% acetic acid at pH 2.5 for 10 min (Vidal and Mello, 2005). Glycoproteins were searched with the periodic acid Schiff (PAS) reaction (Kiernan, 2008).…”
Section: Proteinsmentioning
confidence: 99%
“…However, in this study, the collagen fibers formed a complex with Ponceau SS, an azo dye that aligns its resonating electrons in parallel with the collagen, amplifying the birefringence signal [23,37]. The macromolecular complexes formed by the interaction of Ponceau SS with collagen have characteristics of photonic material [45], and can provide a basis for understanding the relationships between mesophase organization and functionality in biological structures [37,45].…”
Section: Discussionmentioning
confidence: 99%
“…Histological sections were stained with Ponceau SS acidic solution (Sigma-Aldrich), pH 2.5, for 3 min as previously suggested [37]. The evaluations were conducted on an Olympus BX-53P polarized light microscope (Olympus, Tokyo, Japan) equipped with 10 × and 40 × UPLFLN objectives, a 546-nm monochromatic band-pass filter, and a halogen lamp.…”
Section: Birefringence Parametersmentioning
confidence: 99%